1994
DOI: 10.1071/wr9940377
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics of Iophenoxic Acid in Cats and Brushtail Possums.

Abstract: The comparative plasma pharmacokinetics of iophenoxic acid was studied in the cat and brushtail possum (Trichosurus vulpecula) to evaluate the suitability of this compound as a bait marker in these species. In cats, a mean peak plasma concentration of 946 micro g per 100 ml was obtained after administration of 1.5 mg/kg of iophenoxic acid. However, at the same dose level in possums, mean peak plasma concentration was only 157 micro g per 100 ml. Even after administration of 10 mg/kg of iophenoxic acid, the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…However, little consideration has been given to the potential dangers arising from brodifacoum residues in possum carcasses. Metabolism and excretion of foreign compounds such as toxins vary in different species, and the possum shows some idiosyncrasies in its responses (Eason & Jolly 1993;Jolly et al 1994;Eason et al 1994c). In earlier experiments with possums using one-stage prothrombin (OSP) and activated partial prothrombin (APP) times as indicators of susceptibility, we demonstrated that the possum was relatively tolerant to pindone, a first-generation anticoagulant (Eason & Jolly 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, little consideration has been given to the potential dangers arising from brodifacoum residues in possum carcasses. Metabolism and excretion of foreign compounds such as toxins vary in different species, and the possum shows some idiosyncrasies in its responses (Eason & Jolly 1993;Jolly et al 1994;Eason et al 1994c). In earlier experiments with possums using one-stage prothrombin (OSP) and activated partial prothrombin (APP) times as indicators of susceptibility, we demonstrated that the possum was relatively tolerant to pindone, a first-generation anticoagulant (Eason & Jolly 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, IA has been successfully used as a marker in bait acceptance studies in a variety of animal species including carnivores [6][7][8][9][10][11], herbivores [12][13][14][15][16] and omnivores [17] and has been used to determine the feasibility of delivering oral vaccine to wild swine [17] and raccoons [9,24]. Field experiments in which feral pigs (S. scrofa), raccoons (P. lotor), and opossums (D. virginiana) were exposed to IA following ingestion of IA-marked baits were used to confirm the appropriateness of (−)ESI/LC-MS identification in these studies.…”
Section: Field Researchmentioning
confidence: 99%
“…In addition, the extent and duration of IA binding is both species-and dose-dependent. For example, coyotes fed 0.5 mg/kg exhibited elevated iodine levels for approximately 8 weeks [6] while the duration of plasma or serum iodine elevation in stoats was only 2 weeks [21] and in the brushtail opossum and the swamp wallaby it was elevated for less than 2 weeks [11,20]. Dose-dependency has been described in beagle dogs and red foxes which, when fed 20 mg IA, exhibited elevated iodine levels for almost twice as long as those fed 10 mg IA [7].…”
Section: Field Researchmentioning
confidence: 99%
See 2 more Smart Citations